2019
DOI: 10.1177/0958305x19882405
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the air pollution cost of shale gas development in China

Abstract: Shale gas is one of the most promising unconventional hydrocarbon resources in the 21st century. In recent years, economically recoverable reserves have achieved explosive growth, and drilling techniques have made large breakthroughs. As a clean unconventional energy, shale gas is given substantial consideration by governments. However, the cleanliness of shale gas has been questioned for causing serious air pollution during production. To further measure the air pollution cost during the exploration and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Using the ORC power plant model, Some scholars [ 21 ] found that water is more suitable as a thermal fluid than hot oil. Some scholars [ 22 ] studied the influencing factors of shale gas development and utilization using structural equation model, and pointed out that China is a water-scarce country, especially in northern China, where two-fifths of the population only depends on one-fifth of the country's fresh water resources. This is a challenge to dry hot rock development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the ORC power plant model, Some scholars [ 21 ] found that water is more suitable as a thermal fluid than hot oil. Some scholars [ 22 ] studied the influencing factors of shale gas development and utilization using structural equation model, and pointed out that China is a water-scarce country, especially in northern China, where two-fifths of the population only depends on one-fifth of the country's fresh water resources. This is a challenge to dry hot rock development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Where k represents the amount of samples; M represents the number of hidden layer neurons; n represents the number of input layer neurons; m represents the number of output layer neurons; c represents an arbitrary constant in the interval [ 28 , 29 ].…”
Section: Model Designmentioning
confidence: 99%